Adaptive responses to elevated CO2 in fruit species with different phloem loading mechanisms - Davoudi, Marzieh; Kalantzis, Spyridon; Petridis, Antonios (Frontiers in Plant Science, 2024)
Introduction: It has been suggested that the mechanism of phloem loading, that is apoplastic or symplastic loading, may affect a plant's ability to adapt to elevated CO2 levels. Strawberry (Fragaria × ananassa) and tomato (Solanum lycopersicum) are two fruit crops that use different mechanisms to load sugars into the phloem -the former symplastically and the latter apoplastically -yet both species can increase their yields when grown in a CO2-enriched environment. In this study, we subjected strawberry and tomato plants to long-term CO2 enrichment to determine the morphological and physiological adaptations that enable them to increase their yields in response to higher CO2 levels.Methods: Transplanted tomato and strawberry plants were subjected to ambient (400 ppm) and elevated (800 ppm) CO2 for three months. We examined various parameters associated with growth, yield, photosynthesis, and carbon allocation by means of phenotyping, gas exchange analysis, and 13 C labelling combined with isotope ratio mass spectrometry.We found that CO2 enrichment promoted growth and reproductive development in both species, resulting in more flowers per plant (tomato and strawberry), larger crown (strawberry), and, eventually, higher yields. Gas exchange analysis and A/ci curves revealed that elevated CO2 increased carbon assimilation rate in strawberry, but not in tomato -the latter being limited by Rubisco's carboxylation efficiency. Finally, whereas both species prioritized fruit development over the development of other sink organs, they were both limited by carbon export at elevated CO2, since new photoassimilates were equally distributed to various sinks between CO2 treatments.The findings suggest that both species will benefit from future increases in CO2 levels and support current glasshouse practices entailing CO2 enrichment. Those benefits probably stem from an enhanced performance of both species at early developmental stages, as differences in carbon assimilation rate (tomato) and carbon allocation between treatments at late developmental stages were absent. Moreover, crop adaptation to elevated CO2 seems to depend on the ability of each species to respond to elevated CO2, rather than on the phloem loading mechanism per se.